IMPLEMENTASI KEBIJAKAN PEMERINTAH KOTA DALAM PERIZINAN PENDIRIAN RUMAH IBADAH DI KECAMATAN TAMPAN KOTA PEKANBARU TAHUN 2010-2011 - Tinov, M. Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The purpose of this research is to knowing the government implementation decision in licensing the constructing of religion buildings. This research was practiced in Tampan district, Pekanbaru. This research is focused to concord Forum over religion peole. Based from the writer research finding, the license implementation on religion building construction was not good so far, there was any unbalanced and inexpediency like what was written in the join conditions rules between religion department and interior ministry Number 8 and 9, 2006 Revision. The data taken from an interview, documentation and observation, the data analysing technique that used in this research is qualitative method where the writer came to the research location and have interaction with the informant. After that, all of the data will categorized based on the type and usage, after that the data being processed and qualitative-analysed based on the theory and framework, and then the data served in the discussion and commentary form about the city government decision implementation in licensing religion building construction in Tampan district, Pekanbaru, in 2010-2011.The finding the research in 2010: there are 66 unlicensed religion building from 120 religion building. In 2011, there are 51 unlicensed religion building from 179 religion building. The government knew the high number of unlicensed religion buildings that unappropriate with the applied procedure, but they did not take a right action that appropriate with the appropriate rules. Less socialization from city government to realize the religion house manager to make the legitimate religion building license that appropriate with the rules. There are no explanation about the cost in attending the license, there are no definitely processing time while making the license from submit the license until the license got the agreement and done.Keywords: Policy, Implementation, government.